2018
DOI: 10.1186/s12944-018-0691-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum obestatin level strongly correlates with lipoprotein subfractions in non-diabetic obese patients

Abstract: BackgroundObestatin is a ghrelin-associated peptide, derived from preproghrelin. Although many of its effects are unclear, accumulating evidence supports positive actions on both metabolism and cardiovascular function. To date, level of obestatin and its correlations to the lipid subfractions in non-diabetic obese (NDO) patients have not been investigated.MethodsFifty NDO patients (BMI: 41.96 ± 8.6 kg/m2) and thirty-two normal-weight, age- and gender-matched healthy controls (BMI: 24.16 ± 3.3 kg/m2) were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…These findings are in accordance with a study by Zhang et al who suggested that obestatin levels were significantly reduced in obese rodents [18]. In the study of Szentpéteri, they concluded that a reduction of obestatin could contribute to the development of the metabolic syndrome and impaired rate of lipoprotein metabolism in obese patients [19].…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in accordance with a study by Zhang et al who suggested that obestatin levels were significantly reduced in obese rodents [18]. In the study of Szentpéteri, they concluded that a reduction of obestatin could contribute to the development of the metabolic syndrome and impaired rate of lipoprotein metabolism in obese patients [19].…”
Section: Discussionsupporting
confidence: 91%
“…Serum and EDTA plasma samples were kept frozen at −70°C for enzyme-linked immunosorbent assay (ELISA) measurements and for subsequent lipoprotein subfraction analysis. In our work, we followed the methods of Szentpéteri et al [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…LDL subfractions were also detected using Lipoprint System (Quantimetrix Corp., CA, USA) [ 26 ] according to the instructions of the manufacturer. 25 μ l sera were added to polyacrylamide gel tubes along with 200 μ l Sudan Black containing a loading gel solution.…”
Section: Methodsmentioning
confidence: 99%
“…Szentpéteri et al described lower circulating obestatin in NDO patients compared to lean, healthy ones [ 145 ]. Negative correlations were found between BMI, glucose, insulin and HbA1c, VLDL subfraction and obestatin, while HDL-C, ApoAI and mean LDL size correlated positively with obestatin highlighting the possible favorable role of obestatin in morbid obesity.…”
Section: Role Of Novel Hepatokines and Gastrointestinal Hormones In N...mentioning
confidence: 99%